2022
DOI: 10.1155/2022/5157870
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reporting Quality in Randomized Controlled Trials of Acupuncture for Primary Insomnia with CONSORT Statement and STRICTA Guidelines

Abstract: Aim. To assess the reporting quality of randomized controlled trials (RCTs) on acupuncture for primary insomnia (PI). Methods. Seven Chinese and English databases were searched for publication reporting RCTs on acupuncture for PI from the inception of the databases to August 6, 2021. The internationally recognized Consolidated Standards of Reporting Trials (CONSORT) statement and the International Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) guidelines were used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In our investigation, the caliber of reports within the methodology section was inferior relative to other portions, with fewer than one-fifth of RCTs furnishing comprehensive accounts of sample size computations, randomization procedures, and the execution of blinding. This observation aligns with previous evaluations of other RCTs, namely, RCTs of diabetes, CHM formulas, and acupuncture ( Liu X. et al, 2015 ; Zhai et al, 2015 ; Yang et al, 2022 ). Of particular concern, 54 RCTs in the present study did not report the calculations used to determine the sample size.…”
Section: Discussionsupporting
confidence: 91%
“…In our investigation, the caliber of reports within the methodology section was inferior relative to other portions, with fewer than one-fifth of RCTs furnishing comprehensive accounts of sample size computations, randomization procedures, and the execution of blinding. This observation aligns with previous evaluations of other RCTs, namely, RCTs of diabetes, CHM formulas, and acupuncture ( Liu X. et al, 2015 ; Zhai et al, 2015 ; Yang et al, 2022 ). Of particular concern, 54 RCTs in the present study did not report the calculations used to determine the sample size.…”
Section: Discussionsupporting
confidence: 91%
“…Although some researchers argue that the Streitberger needle is more convincing due to the uniqueness of its operation [115], however, the choice of placebo should be rationally designed depending on the direction of the study [114]. In the future, in order to obtain more accurate conclusions and reproducible trial procedures, scholars should strictly follow COSORT and STRICTA guidelines [109]. Of course, from the above, we also predict that the hot research in the future may focus on the design and improvement of acupuncture study protocols and the development and promotion of guidelines for the application of acupuncture [105].…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by a collaboration with the CONSORT group and the Chinese Cochrane Center in 2008 to revise a set of extended CONSORT statements [107]. In recent years, some scholars have used the latest RCT CONSORT statement (https://www.consort-statement.org/) and STRICTA (https://stricta.info/) to evaluate the quality of RCT reports of acupuncture-treated diseases [109][110][111]. Inaccurate randomization and low sample size were identified as the main reasons for low quality in an RCT evaluating the reported quality of acupuncture for low back pain trials from 2010-2020 [22].…”
Section: Bibliometrics Of T100 Articles On Acupuncturementioning
confidence: 99%
“…Svenkerud and MacPherson 29 revealed that the mean STRICTA score increased from 4.27 in the 1994-1995 period to 5.53 in 2014-2015 with an 18% improvement, while the mean CONSORT score rose from 1.01 to 3.32 with an increment of 46%. Previous researchers have evaluated the reporting quality in RCTs concerning various diseases such as cancer 30 and its complications, 31 stroke and poststroke rehabilitation, 32 33 pain, 34 35 primary insomnia, 36 diabetes, 37 chronic obstructive pulmonary disease, 38 herpes zoster 39 and vascular dementia 40 among different languages. 41 A systematic review by Ma et al 27 investigated published RCTs between 2004 and 2012 in China and found that the reporting of the sample estimate (1.2%), ethical committee approval (less than 1%) and conflicts of interest (0%) was inadequate.…”
Section: Discussionmentioning
confidence: 99%